2007
DOI: 10.1088/0957-4484/18/11/115715
|View full text |Cite
|
Sign up to set email alerts
|

Morphology optimization of CCVD-synthesized multiwall carbon nanotubes, using statistical design of experiments

Abstract: The possibility of optimization of morphological features of multiwall carbon nanotubes (MWCNTs) using the statistical design of experiments (DoE) is investigated. In this study, MWCNTs were synthesized using a catalytic chemical vapour deposition (CCVD) method in a horizontal reactor using acetylene as the carbon source. The effects of six synthesis parameters (synthesis time, synthesis temperature, catalyst mass, reduction time, acetylene flow rate and hydrogen flow rate) on the average diameter and mean rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…As a result, they proposed that temperature is a dominating factor for CNT diameter control. The same conclusions have been also reported by other researchers [9,10,25,[69][70][71]. The main effects of increasing the reaction temperature are to increase the metal particle size during the CVD growth of CNTs, and consequently the nanotube diameter.…”
Section: Temperaturesupporting
confidence: 88%
See 1 more Smart Citation
“…As a result, they proposed that temperature is a dominating factor for CNT diameter control. The same conclusions have been also reported by other researchers [9,10,25,[69][70][71]. The main effects of increasing the reaction temperature are to increase the metal particle size during the CVD growth of CNTs, and consequently the nanotube diameter.…”
Section: Temperaturesupporting
confidence: 88%
“…The most commonly used carbon sources are ethylene [13,32,50,75,76], acetylene [16,33,47,58,70], methane [28,41,42,51,54,61,63], ethanol [19,30,64,80] and CO [21,46]. Recently, Yen et al [84] reported that CNTs could be synthesis from solid-stated polymers-polycarbosilane and polyethylene using FBCVD.…”
Section: Carbon Feedstockmentioning
confidence: 99%
“…Several authors have the same conclusions as our results [19][20][21]. However others have conflicting results for the impact of temperature gradient on the diameter of tubes.…”
Section: A Structure Characterizationsupporting
confidence: 86%
“…In systems using a different carbon source, carbon yield with respect to reaction temperature shows the same trend, but optimal reaction temperatures vary (Morancais et al, 2007;Philippe et al, 2009;Son et al, 2008). In addition, CNT diameter and crystallinity vary depending on the reaction temperature (Muataz et al, 2006;Andrews et al, 2002;Kim et al, 2005;Nourbakhsh et al, 2007;Xiong et al, 2005;Yao et al, 2004). These results suggest that each system requires reaction temperature optimization.…”
Section: Introductionmentioning
confidence: 92%